Parity as radical pragmatism: Centering farm justice and agrarian expertise in agricultural policy - Graddy-Lovelace, Garrett; Krikorian, Jacqueline; Jewett, Andrea; Vivekanandan, Avinash; Stahl, Katherine; Singh, Indra Shekhar; Wilson, Brad; Naylor, Patti; Naylor, George; Pennick, Edward Jerry (Frontiers in Sustainable Food Systems, 2023)
Rather than treating symptoms of a destructive agri-food system, agricultural policy, research, and advocacy need both to address the root causes of dysfunction and learn from longstanding interventions to counter it. Specifically, this paper focuses on agricultural parity policies – farmer-led, government-enacted programs to secure a price floor and manage supply to prevent the economic and ecological devastation of corporate unfettered agro-capitalism. Though historically underrepresented through lenses of colonialism, classism, and racism, swaths of humanity are continuing to mobilize, especially in India, calling for agri-food systems transformation, farmgate pricing protections, and collective bargaining across the globe. Parity, a movement built on principles of fair farmgate prices and cooperatively coordinated supply management, are mostly considered ‘radical,’ deemed inefficient, irrelevant, obsolete, and grievous government overreach—from the vantage of a system that profits from commodity crop overproduction and agroindustry consolidation. However, by examining parity through a producer-centric lens cognizant of farmers’ ability, desire, and need to care for the land, ideas of price protection and supply management become foundational, so that farmers can make a dignified livelihood stewarding land and water while producing nourishing food. This paradox—that an agricultural governance principle can seem both radical and common sense, far-fetched and pragmatic—deserves attention and analysis. When farmers have been placed on the margins of survival, their voices are absent from these conversations, leaving space for worldviews favoring de-agrarianization altogether. Apart from the history of parity price system in US, the paper will examine an off-shoot of parity program in India – the Minimum Support Price (MSP) system.This paper will explain the parity price system as a dynamic idea with offshoots in the Global South, and is currently the principal demand from the agrarian community. Farmers want to make MSP/fair- prices a legal right for farmers, resisting against the agro-capitalistic forces working to dismantle the economic and social safeguards offered by grain reserves, price supports and pathways of collective bargaining. From East India to the plains of the United States, parity offers a pragmatic solution to global agro-industrial corporate capture, poor labor conditions, environmental destruction, and promotes broader food sovereignty globally.